FAKTOR – FAKTOR SERTA ALASAN YANG MENYEBABKAN TINGGINYA ANGKA CERAI GUGAT - Widodo Widodo (RECHTSTAAT, 2014)
The factors and reasons in Divorce Petition that can become the basis of your divorce petition in Religion Court include: “Husband makes sexual intercourse outside of marriage, is a drunker, drug abuser, gambler, and etc; he has left you for 2 (two) successive years without license or clear and right reason; it means that the husband consciously and deliberately leaves you, he is imprisoned for 5 (five) years or more after marriage, he does violence and like to treat you poorly, he cannot undertake his obligation because of his disability or disease, the incidence of ongoing dispute and quarrel without the probability of concord, the husband breaks the taklik-talak he had said during ijab-kabul, he converts leading to discordance within family. The research method employed was descriptive one. As a prescriptive research, this current research studied legal objective, justice value, rule of law validity, legal concepts and legal norms. This descriptive research aimed to describe systematically a certain population or area. The descriptive research was intended to provide prior data as thorough as possible about human, condition or other phenomenon. The qualitative data analysis was a research method providing descriptive data in which what the respondents say in either written or spoken form and what they do actually were investigated and studied as something intact. The legal rationales the Judge made still referred to legislation or government decision or enacted rule norms such as Law No.1 of 1974, Islamic Law Compilation (KHI), Civil Code and Herzien Inlandsch Reglement (HIR), and etc. It means that the Judge’s rationales in deciding the divorce (petitioning divorce) case considered firstly the posita and petitum existing in the petition. Then, the facts in the trial and the evidence brought into trial, either written or spoken (witness), were also taken into account. Meanwhile, non-legal rationale was made by the Judge as the attempt of confirming and clarifying the existing legislation in order to be consistent with the expectation; these rationales included usefulness, economic, time or effectiveness, and so on. Secondly, there were two perspectives on the effectiveness of petitioning divorce verdict implementation in Religion Court: society perspective and court perspective. In society perspective, a petitioning divorce verdict was considered as ineffective because it was not realized as due. It means that the wife’s rights as included in the verdict were frequently unfulfilled by the husband (former husband). Meanwhile, in Religion Court perspective, the result of verdict made and imposed to the parties was considered as effective because no report from the parties on the right or obligation denial by one party. Keywords: Petitioning Divorce Factor, Petitioning Divorce Reason, Divorce Petition.